Effects of meal or pellet diet form on finishing pig performance and carcass characteristics - M L Potter; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
Two experiments were performed to determine the effects of feeding diets in meal or pellet form on finishing pig performance. A corn-soybean meal-based diet was fed in Exp. 1, and a diet containing alternative ingredients was used in Exp. 2. All pelleted diets were processed through a CPM pellet mill (California Pellet Mill Co., Crawfordsville,IN) equipped with a 3/16 in. die. In Exp. 1, a total of 1,072 pigs (60.7 lb) were used in a 112-d trial. Treatments were arranged in 2 × 2 factorial design (10 pens per treatment) with main effects of diet form (meal or pellet) and gender (barrows or gilts). Diet formulation and particle size (approximately 660 microns) was identical among the treatments. From d 0 to 112, pigs fed pelleted diets had increased ADG (2.04 vs. 1.92 lb, P<0.01) compared with pigs fed diets in meal form. There was no difference (P = 0.69) in ADFI, but pigs fed pelleted diets had a 5.3% improvement (2.68 vs. 2.83, P<0.01) in F/G compared with pigs fed meal diets. With the improvements in F/G driving the growth response, pigs fed pellets were 13.6 lb heavier (P<0.01) at off test than pigs fed meal diets. In Exp. 2, a total of 1,214 pigs (58.3 lb) were used in a 42-d trial to evaluate diets containing alternative ingredients in pellet or meal form. Barrow and gilt pens were randomly allotted to a meal or pellet treatment group (11 pens per treatment). Like Exp. 1, diet particle size (approximately 660 microns) and formulation were identical among the treatments. Pigs fed a by-product-based diet in pellet form had greater (2.05 vs. 1.95 lb, P<0.01) ADG than pigs fed the identical diet in meal form. There were no differences (P â‰¥ 0.15) in overall (d 0 to 42) ADFI or F/G between pigs fed meal and pelleted diets. Pigs fed pelleted diets had a numerical (P = 0.14) weight advantage of 4.1 lb on d 42 compared with pigs fed meal diets. These data demonstrate that feeding a pelleted diet improved ADG compared with feeding a meal diet; however, the magnitude of the response was inconsistent between trials. In addition, F/G was improved by pelleting in the first trial, with no effect found in the second trial. One explanation for this difference might be the quality of the pellets. Samples of the pelleted diets collected in Exp. 1 contained approximately 25% fines, whereas samples of the pelleted diets in Exp. 2 were composed of approximately 35% fines. Diets formulation (corn-soybean vs. corn-alternative ingredients) can influence pellet quality, which may explain differences between the experiments.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Carcass; Growth; Pellet; Swine